Justicia transicional, derechos humanos y marco institucional en los nuevos escenarios políticos en México - Laura Loeza Reyes (Les Cahiers ALHIM)
This article analyzes the importance and relevance of the public policy for transitional justice that was desiged and promoted in Mexico by family groups related to victims of violence and also by national and international human rights organizations and experts from academia. The two primary factors taken into consideration are the humanitarian crisis caused by the «fight against organized crime» policy –which was based on the militarization of police activities, was implemented more than a decade ago, and has left tens of thousands of victims– and the complex and adverse situation the implementation of such a policy faces in light of the current Mexican president’s ignorance on human rights topics. The article explains why a transitional justice policy is the only way to turn around the complex problem of violence in Mexico and to channel the country’s political processes towards the rule of law.